Analisis partisipasi ibu balita dalam pemanfaatan Posyandu di wilayah Puskesmas Kota Banda Aceh - Siti Fatimah; Asnawi Abdullah; Amin Harris (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Public participation generally seen as a form of health behavior is the participation of mothers of children under five in the of Maternal & Child Health Centre it program. Its is a form of integrated services organized for and by the community with work programs from related agencies to then obtain basic health services, decrease maternal and child mortality rates and for the achievement of Small Prosperous Happy Families (KKBS).Purpose: The study aims to analyze the coverage of weighing children under five to Maternal & Child Health Centre (D/S) in the area of the Banda Aceh City Health Center.Method: This research is a qualitative study with a descriptive approach conducted with a Focus Group Discussion (FGD) of 3 main informants, 4 implementing informants and 7 policy makers in the lowest D / S region (Lampaseh Puskesmas area) and 3 main informants, 4 implementing informants and 8 informants policy makers in the highest D/S region (Kopelma Darussalam Puskesmas area).Results: The results of this study found that the availability of facilities is still limited, the role of cadres is still low (not yet able to carry out development programs), the role of the gampong government is still lacking in supporting the implementation and improvement of posyandu visits, policy makers do not fully understand that the conditions in posyandu are a big responsibility from the village, and in practice in the field there has not been an effort to monitor and evaluate the extent of the implementation of the posyandu by the health department.Conclusion: The cadres' low knowledge of development programs in an effort to increase community motivation for posyandu visits. Suggestions for implementing of Maternal & Child Health Centre activities to provide an understanding of how to implement a Maternal & Child Health Centre, improve competence, provide suggestions for development programs and for policymakers.